THE USE OF QUIVER AS VISUALIZATION OF MODULES OVER ALGEBRAS - RACHMAN INAK (NIM : 10108044); Pembimbing : Dr. Muchtadi Intan Detiena, AULIA
Let K be an algebraically closed field and A be a basic, connected, finite dimensional K-algebra. By using a bound quiver (Q,I) associated to A, in this work we explain how any A-module M can be visualised as a K-linear representation of (Q,I), which is, a family of K-vector space Ma, for any point a in Q, connected by K-linear maps rho alpha : Ma -> Mb corresponding to arrows alpha : a -> b di Q, and satisfying some relations induced by I.